THE VALIDITY OF USING NOMINEE BY NOTARIES TO MEET THE REQUIREMENTS FOR APPLYING THE LIMITED LIABILITY COMPANY CREDIT IN BANKING - Winahyu Erwiningsih (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The legal principles of contract freedom, pacta sunt servanda, and reciprocal good faith are the cornerstones of nameless agreements, or inomonaat, which include nominee agreements. The provisions of the nomination agreement are enforceable against the parties who enter it as well as by the courts if it is legitimate and contains the clauses needed by law, custom, and appropriateness. Banks believe that adding a Nominee Agreement signed in front of a Notary Public will strengthen the PT's guarantee given as a debtor and function as a lawful deed with unblemished probative power. The holding of freehold land by a Limited Liability Company utilizing the Deed of Land Ownership Statement (Nominee) may be seen as legal smuggling even though the people who made the deed agreed to its conditions. An agreement is illegitimate and void if it is founded on an illegal reason. Notaries must be aware of any existing rules regulating the substance of nominee agreements when drafting them. Notaries are responsible for the actions they take since they are general officials who conduct acts. A notary may face repercussions if a deed does not adhere to the relevant Law. Financial institutions are adaptable in the primary principle of not requiring guarantees from potential clients when they apply for funding in any way, therefore it is safe to assume that cost loan transactions through financial institutions will go smoothly. Consequently, if this can be executed successfully by banks, real smuggling attempts by other companies or debtors via nominee agreements can be decreased.